PENGARUH PENDEKATAN DEEP LEARNING TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS IX DI SMPN 20 KUPANG - paulin dairo; Sukmawati Sukmawati; Ahmad Hamado; Jusuf Ariyanto Amheka (Jurnal Geografi, 2026)
Students' critical thinking skills are essential competencies in Social Studies learning. However, the critical thinking skills of Grade IX students at SMPN 20 Kupang were relatively low, as indicated by pretest scores below the minimum mastery standard. This study aimed to examine the effect of the Deep Learning approach on improving students' critical thinking skills. The research employed a quantitative quasi-experimental method using a Non-Equivalent Control Group Design. The sample consisted of 60 students, divided into an experimental group (Class IX B, 30 students) and a control group (Class IX A, 30 students). Data were collected through observation, documentation, and pretest-posttest assessments, then analyzed using descriptive statistics, normality and homogeneity tests, and the Paired Sample T-Test with SPSS. The results showed that the experimental group achieved a higher average posttest score (83,33) than the control group (77,67). Statistical analysis confirmed that the Deep Learning approach significantly improved students' critical thinking skills in Social Studies learning.